A model to select processes for IT service management improvement - Shrestha, A.; Cater-Steel, A.; Tan, Wui-Gee; Toleman, M. (Deakin University, 2012)
IT organisations are continually seeking improvements in managing IT service management processes. The selection of relevant processes to improve is one of the most crucial initial decisions to make in service improvement projects. In this paper, we focus on developing a process selection decision model using service perception factors from the Service Quality (SERV-QUAL) model and business drivers from the Balanced Scorecard perspectives along with the main objective of service improvement as improvement driver. We use a Design Science Research method to develop the model and then a prototype from our proposed model. We establish an evaluation protocol to determine the effectiveness of the prototype which will be demonstrated in a case organisation. The main contribution of the paper is to provide evidence-based decision support for IT service providers to select the most relevant service processes to improve.